1995
DOI: 10.1152/jappl.1995.78.5.1679
|View full text |Cite
|
Sign up to set email alerts
|

Sensory nerve- and neuropeptide-mediated relaxation responses in airways of Sprague-Dawley rats

Abstract: We examined the role of sensory nerves in mediating nonadrenergic inhibitory responses in airway segments isolated from male Sprague-Dawley rats. In the presence of adrenergic blockade, capsaicin (Cap; 1 microM) elicited marked relaxation responses in isolated bronchi precontracted with bethanechol (Beth). Cap-induced inhibitory responses were unaffected by tetrodotoxin (TTX), were attenuated by incubation of the airway with indomethacin (Indo), phosphoramidon, or RP-67580, but were abolished by previous expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
29
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 0 publications
10
29
0
Order By: Relevance
“…Capsaicin induced concentration-dependent relaxation responses in mouse isolated trachea, consistent with previ- ous studies in rodent bronchial preparations (Manzini, 1992;Szarek et al, 1995Szarek et al, , 1998. Capsaicin-induced relaxation responses in mouse trachea are most likely mediated by TRPV1 because they were abolished by the TRPV1 antagonist capsazepine.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Capsaicin induced concentration-dependent relaxation responses in mouse isolated trachea, consistent with previ- ous studies in rodent bronchial preparations (Manzini, 1992;Szarek et al, 1995Szarek et al, , 1998. Capsaicin-induced relaxation responses in mouse trachea are most likely mediated by TRPV1 because they were abolished by the TRPV1 antagonist capsazepine.…”
Section: Discussionsupporting
confidence: 85%
“…Previously published studies have used epithelium denudation techniques to establish the importance of the epithelium in relaxation responses to capsaicin (Szarek et al, 1995(Szarek et al, , 1998 and SP (Szarek et al, 1995(Szarek et al, , 1998Kao et al, 1999;Liu et al, 2006) in rat and mouse isolated airway preparations. Moreover, Szarek et al (1998) demonstrated that epithelium removal by mechanical disruption blocked both capsaicin-and SP-induced release of PGE2.…”
Section: Discussionmentioning
confidence: 99%
“…In rat trachea, the importance of the presence of the epithelium and the NK 1 receptor has been demonstrated. Through the use of specific inhibitors and measurements of mediator release, PGE 2 was found to be the relaxing factor [10,15,33]. This phenomenon has also been described in mice.…”
Section: Discussionmentioning
confidence: 74%
“…Such histopathologic changes of Influenza A-infected tracheal epithelium were observed in the current study, with desquamation and regional epithelial shedding likely having functional consequences on the epithelium. A dependency of smooth muscle relaxation responses on an intact epithelium has been unequivocally demonstrated for several relaxants including capsaicin [20,33] and SP [34,35] whereby relaxation responses were substantially diminished or completely abolished by either mechanical or viral-induced disruption of the epithelium. In view of the intermediary role of the epithelium in acrolein-induced relaxation responses, in combination with the well-established effects of Influenza A on the epithelium, the airway epithelium represents an obvious target for modulation of relaxation responses by Influenza A.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, acrolein has been reported to evoke powerful relaxation responses in precontracted mouse isolated tracheal segments via an epitheliumdependent mechanism through the release of the arachidonic acid metabolite prostaglandin E 2 (PGE 2 ) [19]. These relaxation responses are thought to form part of a regulatory 'sensory inhibitory system' proposed to be involved in the negative regulation of smooth muscle contraction in a number of rodent species, including mouse and rat [19][20][21], where a balance between bronchoconstriction and relaxation may serve to regulate airway patency. Thus, damage to the epithelium and consequent loss of the negative regulation of smooth muscle contraction may contribute to the generation of a hyperreactive airway.…”
Section: Introductionmentioning
confidence: 99%